An experimental study into the effects of bulk and flow behaviour of laser sintering polymer powders on resulting part properties - Ziegelmeier, Stefan; Christou, Panagiotis; Wöllecke, Frank; Tuck, Christopher; Goodridge, Ruth D.; Hague, Richard J.M.; Krampe, Erhard; Wintermantel, Erich (Elsevier, 2015)
The properties of parts manufactured by laser sintering (LS) are, amongst others, influenced by the packing and flow efficiencies of the powders being processed.